Long-Term Socio-Ecological Legacies of Colonial Irrigation in Lampung, Indonesia (1935–1993) - Shadra, M. Nehza Rausan; Akmansyah, Muhammad; Nurnazli, Nurnazli (Analisis Sejarah, 2026)
This study evaluates the socio-ecological consequences of the Argoguruh Dam irrigation system from the Dutch colonial era (1935–1942) through the New Order period (1993). Using an environmental history approach informed by Richard Grove’s Green Imperialism and path-dependency perspectives, the study examines the historical background of the project, its social and environmental impacts, and the long-term continuity of those impacts. A qualitative, library-based method was employed using colonial newspapers, government reports, and local newspapers such as Berita Yudha and Harian Ekonomi Neraca. The findings show that the Argoguruh Dam significantly increased rice production and accelerated the expansion of transmigrant settlements in Trimurjo–Metro. At the same time, the project contributed to large-scale deforestation, watershed sedimentation, and the marginalization of indigenous Lampungese communities. These socio-ecological transformations persisted into the New Order era through irrigation rehabilitation projects, transmigration expansion, and mega-agrarian development schemes.